Evaluation of sustainability and the impact of the agriculture styles of the chilean coastal dry lands - González Ulibarry, Paco; García Elizalde, Pedro; Gastó Corderch, Juan; De Kartzow Garcia, Alejandro; Obando-Ulloa, Javier Mauricio (My University, 2017)
Agriculture has been progressing continuously, from the use of free natural resources to the fossil fuels as energy sources. Even though agriculture depends mainly on ecosystem resources and services, its development has been apparently centered only on yield, not considering neither the ecological value of the negative externalities nor the decapitalization of the resources that influence sustainability. Thus, the information on the evaluation of the sustainability on different agriculture styles is scarce or almost null. This investigation evaluates the sustainability in different agriculture styles (intensive horticulture, traditional farm and self-sustaining horticulture) established in Hualqui (Region of Biobío, Chile), through the energy flows present on each style to measure the impact generated on the land. The results revealed that the self-sustaining horticulture style showed a higher sustainability compared to the traditional farm and intensive horticulture style. These results can contribute to the public, policies to reorient the action strategy to encourage the sustainability in the different agriculture styles.
Keywords: Emergy; Horticulture; Emergy index; Cultural landscape